Optimization of ICRH for core impurity control in JET-ILW. (19th February 2016) - Lerche, E.; Goniche, M.; Jacquet, P.; Van Eester, D.; Bobkov, V.; Colas, L.; Giroud, C.; Monakhov, I.; Casson, F.J.; Rimini, F.; Angioni, C.; Baruzzo, M.; et al.
Abstract: Ion cyclotron resonance frequency (ICRF) heating has been an essential component in the development of high power H-mode scenarios in the Jet European Torus ITER-like wall (JET-ILW). The ICRF performance was improved by enhancing the antenna-plasma coupling with dedicated main chamber gas injection, including the preliminary minimization of RF-induced plasma-wall interactions, while the RF heating scenarios where optimized for core impurity screening in terms of the ion cyclotron resonance position and the minority hydrogen concentration. The impact of ICRF heating on core impurity content in a variety of 2.5 MA JET-ILW H-mode plasmas will be presented, and the steps that were taken for optimizing ICRF heating in these experiments will be reviewed.